Is a 3 mm Surgical Margin Safe for Basal Cell Carcinoma in the Head and Neck that is Less than 2 cm, Considering Different Risk Factors? - Min-Jun Yong; Seok-Ju Yoo; Hea-Kyeong Shin (Archives of Plastic Surgery)
Background Basal cell carcinoma (BCC) is the most common type of nonmelanoma skin cancer. Typically, resection requires a safety margin of ≥4 mm. When removing tumor cells, achieving complete excision with minimal safety margins and reconstructing the defect to preserve the original appearance are important. In this study, we used a 3-mm resection margin to confirm recurrence and re-resection rates.